Male C57BL6/N and C57BL6/J Mice Respond Differently to Constant Light and Running-Wheel Access - Capri, Kimberly M.; Maroni, Marissa J.; Deane, Hannah V.; Concepcion, Holly A.; DeCourcey, Holly; Logan, Ryan W.; Seggio, Joseph A. (Frontiers in Behavioral Neuroscience, 2019)
Previous studies have shown that exposure to circadian disruption produces negative effects on overall health and behavior. More recent studies illustrate that strain differences in the behavioral and physiological responses to circadian disruption exist, even if the strains have similar genetic backgrounds. As such, we investigated the effects of constant room-level light (LL) with running-wheel access on the behavior and physiology of male C57BL6/J from Jackson Laboratories and C57BL6/N from Charles River Laboratories mice. Mice were exposed to either a 12:12 light-dark (LD) cycle or LL and given either a standard home cage or a cage with a running-wheel. Following 6 weeks of LD or LL, their response to behavioral assays (open-field, light-dark box, novel object) and measures of metabolism were observed. Under standard LD, C57BL6/J mice exhibited increased locomotor activity and reduced exploratory behavior compared to C57BL6/N mice. In LL, C57BL6/J mice had greater period lengthening and increased anxiety, while C57BL6/N mice exhibited increased weight gain and no change in exploratory behavior. C57BL6/J mice also decreased exploration with running-wheel access while C57BL6/N mice did not. These results further demonstrate that C57BL/6 substrains exhibit different behavioral and physiological responses to circadian disruption and wheel-running access.